Induced Resistance Using Nonpathogenic Fusarium Oxysporum for Biological Control of Banana Fusarium Wilt - Elsharif, Tarig Elsayed Ali (2003)
Banana (Musa spp. Linn.) is the second most important fruit crops in Malaysia. It is easily attacked by the fungus Fusarium oxysporum Schlect. fsp. cubense (E.F.Smith) Snyder and Hansen (FOC), causing terminal wilt in the field. Chemical and cultural methods were not effective in controlling the disease. Therefore, alternative control measures have to be developed. In recent years, nonpathogenic Fusaria was being considered for plant disease control and could be the most promising approach for biological control of Fusarium wilt in banana through induced systemic resistance. Isolates of nonpathogenic F oxysporum (FO: F01, F02, F03, F04, F05 and F06) were isolated from healthy roots and rhizospheres of bananas vars. Berangan and Rastali, and were identified to the species level based on cultural and morphological characteristics. Random amplified polymorphic (RAPD-PCR) analysis was able to establish variability within F. oxy.\porom isolates and between saprophytic and pathogenic fonns (FOe race 1 and race 4), using ope 11 and ope 14 primers. All 6 isolates of FO were antagonistic to both pathogenic race 1 and race 4 of FOe with values of the % of inhibition of radial growth (PIRG) exceeding 50% in a series of dual culture test. F04 was found to be the most antagonistic against FOC' race 4 with PIRGof65%. Infectivity studies on six-weeks-old tissue cultured banana seedlings var. Berangan cv. intan, con finned that FO1, F02, F03, F04, F05 or F06 were not pathogenic to banana seedlings. No visible foliar or internal symptoms were observed both on inoculated and control seedlings. Seedlings inoculated with FOC' race 4 produced foliar symptoms as yellowing of the older leaves followed by necrosis and wilting. F04 conferred some degree of resistance to the host when challenged with FOe race I suggesting the possible role of induced resistance against Fusarium wilt.